GAMBARAN PERILAKU (PENGETAHUAN, SIKAP, DAN PERILAKU) PENCEGAHAN GASTROESOPHAGEAL REFLUX DISEASE (GERD) PADA MAHASISWA - Ariyani, Fitri; Martini, Martini; Hestiningsih, Retno; Fauzi, Muh (Jurnal Kesehatan Masyarakat, 2024)
Gastroesophageal Reflux Disease (GERD) is a chronic disease and is common in society, especially in adults. Activities for students are so dense, such as lectures, thesis writing, and other activities that there are more risk factors for GERD. The purpose of this study was to describe the behavior of prevention of Gastroesophageal Reflux Disease (GERD) in Diponegoro University Semarang students. This research is a cross-sectional study, with respondents as many as 193 students aged 17-25 years who were selected through accidental sampling. Data collection was carried out by filling out a questionnaire which was distributed via gform. Data were analyzed univariately. The results showed that there were 58 respondents who suffered from GERD (30.1%), the majority of whom were female, namely 55 people (32%). A total of 119 respondents (61.7%) had a good level of knowledge, 103 respondents (53.4%) had a positive attitude, and 115 respondents (59.6) had good prevention practices against GERD. Good knowledge and attitudes that are carried out consistently regarding GERD prevention will make it easier for someone to carry out good GERD prevention practices as well